Knife and bulldozer bottom blade interaction with soil at the beginning of a pass - V. A. Nikolayev (Вестник СибАДИ)
Introduction. At the beginning of the production of road construction works, it is necessary to remove stones, bushes, trees from the right-of-way of the future road. To perform such work, it is advisable to use cyclic units, in particular, with bulldozer equipment. Interaction with the soil of the knife and the blade of the bulldozer is accompanied by a complex of interrelated processes. These processes complicate the theoretical analysis of the interaction of the knife and the bottom part of the blade of bulldozer equipment with the soil. Therefore, despite the large number of publications, the interaction of the knife and the bottom part of the blade of bulldozer equipment with the soil is not analyzed in sufficient details. Meanwhile, without a detailed analysis of this interaction, it is difficult to modernize bulldozer equipment.The method of research. Interaction with the soil of the knife and the blade of the bulldozer has two features. First, the knife of a bulldozer with a straight blade is installed perpendicular to the direction of movement of the unit, so the bulldozer knife carries out energy-intensive cutting of the soil. Secondly, the cut layer of soil moves the pile of the bulldozer in front of it. The concave shape of the surface of the working body causes a concave mapping of crumple stresses, leading to the appearance of a zone of volumetric compression of the soil, which increases more and more during the movement of the unit. Both the deviator and ball components of the stress tensor in the ground increase. Therefore, the front surface of the knife is divided into a blade and a plane that carries out, together with the plane of the lower part of the blade, the displacement of the primary displaced soil. It is necessary to consider separately the impact on the ground of the blade, the edge of the knife and the front surface of the knife and the lower part of the blade.Results. From the drawings the length of the trace of the surface of the pseudo-displacement of the soil in the longitudinal-vertical section, the area of the primary ground shift with the edge of the knife, the area of impact on the ground of the knife surface, the area of impact on the ground of the surface of the lower part of the blade are determined. The area of pseudo-displacement of the soil and the area of displacement of the primary shifted soil were calculated. The dependencies of the areas on the recess of the bulldozer knife are constructed.Conclusion. As the depth of the bulldozer knife increases, the area of pseudo-displacement of the soil by the surface of the knife, the area of primary ground shear with the right or left edge of the knife increases linearly. In this case, the displacement area of the primary shifted soil increases by the parabola. Identifying the area of the pseudo-displacement of the soil, the area of the primary ground shift with the right or left edge of the knife and the displacement area of the primary shifted soil will determine the energy costs required to affect the surface of the knife and the lower part of the blade on the ground.